STRATEGI PEMBINAAN TERITORIAL KODIM 1603/SIKKA DALAM MEWUJUDKAN KETAHANAN WILAYAH MENGHADAPI ERUPSI GUNUNG LEWOTOBI LAKI-LAKI [TERRITORIAL DEVELOPMENT STRATEGY OF MILITARY DISTRICT COMMAND 1603/SIKKA IN STRENGTHENING REGIONAL RESILIENCE AGAINST THE ERUPTION OF MOUNT LEWOTOBI LAKI-LAKI] - Permana, Denny Riesta; Taufik, Robby M.; Purwanto, Sigit (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
This study examines the territorial development strategy implemented by Military District Command 1603/Sikka (Kodim 1603/Sikka) in strengthening regional resilience to face the eruption of Mount Lewotobi Laki-Laki. The research aims to analyze the effectiveness of the Pembinaan Teritorial (Binter) strategy as part of Indonesia’s total defense system in responding to nonmilitary threats such as natural disasters. Using a qualitative descriptive approach, data were collected through field observations, interviews, and documentation with Kodim officers, local government, and disaster management agencies. The results show that the Binter strategy effectively strengthens social and physical resilience through three pillars: social communication, territorial defense empowerment, and community engagement. Kodim 1603/Sikka plays a crucial role as a coordination hub, bridging the synergy between local government, BPBD, and the community to enhance preparedness and adaptability. The study concludes that territorial development, when integrated with disaster management, significantly contributes to an adaptive and participatory regional defense model.